2016
DOI: 10.1167/16.7.10
|View full text |Cite
|
Sign up to set email alerts
|

Detection of periodic motion trajectories: Effects of frequency and radius

Abstract: Periodic trajectories are an important component of biological motion. Or, Thabet, Wilkinson, and Wilson (2011) studied radial frequency (RF) motion trajectory detection and concluded that, for RF2-5 trajectories, the threshold function paralleled that of static RF patterns. We have extended Or et al.'s (2011) findings to a broader range of RFs (three to 24 cycles) and across a 4-fold range of radii (1°-4°). We report that (a) thresholds for RF trajectories decrease as a power function of RF for low RF traject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 62 publications
(106 reference statements)
1
4
0
Order By: Relevance
“…Therefore, it is unclear how the information is being processed early in the visual stream, but our results do suggest that integration of this motion-defined information occurs in the same manner as for contour-defined information. Perhaps, as suggested by Wilkinson et al (2016), the motion RFs are providing a signal to higher levels of the ventral visual stream resulting in the similarity of results found between contour-defined RF patterns and motiondefined RF patterns found in the current study and by Wilkinson et al (2016).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Therefore, it is unclear how the information is being processed early in the visual stream, but our results do suggest that integration of this motion-defined information occurs in the same manner as for contour-defined information. Perhaps, as suggested by Wilkinson et al (2016), the motion RFs are providing a signal to higher levels of the ventral visual stream resulting in the similarity of results found between contour-defined RF patterns and motiondefined RF patterns found in the current study and by Wilkinson et al (2016).…”
Section: Discussionsupporting
confidence: 83%
“…Recent work has shown a number of similarities between motion RFs and static RF patterns (Wilkinson et al, 2016). They found that thresholds increase proportional to the pattern's radius and thresholds decrease as a function of increasing RF number, which conforms to a power-law relationship, both of which have been shown for static RF patterns (Wilkinson et al, 1998).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…The results of Rossit et al are consistent with the idea that action and perceptual pathways are different (Goodale & Milner, 1991;Goodale & Milner, 1992;Milner & Goodale, 2008) and, therefore, may have differing visual field biases (Danckert & Goodale, 2003). Additional evidence also comes from Wilkinson, Haque, Or, Gottlieb, and Wilson (2016), who also find no difference in sensitivity to motion-defined RF patterns when presented in either the upper or lower visual field. Although these patterns are defined by motion, the pattern of results for changes in frequency, radius, and cycles of modulation are highly similar to static RF patterns.…”
Section: Discussionmentioning
confidence: 95%